Payment system innovations and financial intermediation: The case of Indonesia - Alexander Lubis; Constantinos Alexiou; Joseph G. Nellis (Asian Development Bank Institute (ADBI), 2019)
This paper explores the relationship between innovations in payment systems and financial intermediation. By focusing on excess reserves and the currency demand, we provide evidence on the extant transmission mechanism. In this direction, we applied the generalized method of moments (GMM) and vector error correction model (VECM) techniques to a dataset collated for Indonesia. We found that the currency demand affects financial intermediation whilst observing a limited role of excess reserves in affecting financial intermediation. We discovered that credit card payments have a statistically significant effect on the currency demand, whereas debit card payments only influence financial intermediation in the long run. In addition, the real-time gross settlement (RTGS) exerts upward pressure on excess reserves. The findings are of great importance, as they provide support for policies that favor payment migration to an electronic platform, particularly that of card-based payment systems.
Keywords: E42; E58; N25; G21; 330; payment systems; financial intermediation; excess reserves; currency demand; monetary policy